The impact of high-pressure processing treatment on microbial inactivation of seafood – a review - Romulo, A. (2023)
Seafood is categorized as high perishable food and commonly contaminated by foodborne pathogens such as bacteria and viruses. The heat processing treatment is usually applied to improve the quality and safety of seafood products and give detrimental impact to the sensory and nutritional quality. High pressure processing (HPP) has been described as an excellent alternative method to inactivate numerous bacteria and viruses in seafood products, while the organoleptic and nutritional properties could be maintained like a fresh product. HPP has been explored for a wide range of parameters operation, which is specific for each bacteria and viruses. HPP usually runs at the pressure range of 100-600 MPa with the holding time range of 1-60 mins. This review summarized the principle of high-pressure processing treatment and research findings, which emphasized the association between HPP treatment and food-borne pathogen reduction in seafood. The success of HPP treatment to inactivate foodborne pathogens depends on the optimization of parameters operation in order to spread this method to more applicable in seafood industries.